Composable scheduler activations for Haskell. (27th June 2016) - SIVARAMAKRISHNAN, K. C.; HARRIS, TIM; MARLOW, SIMON; PEYTON JONES, SIMON
Abstract: The runtime for a modern, concurrent, garbage collected language like Java or Haskell is like an operating system: sophisticated, complex, performant, but alas very hard to change. If more of the runtime system were in the high-level language, it would be far more modular and malleable. In this paper, we describe a novel concurrency substrate design for the Glasgow Haskell Compiler that allows multicore schedulers for concurrent and parallel Haskell programs to be safely and modularly described as libraries in Haskell. The approach relies on abstracting the interface to the user-implemented schedulers through scheduler activations, together with the use of Software Transactional Memory to promote safety in a multicore context.